Traditional Chinese Medicine in Treating Primary Podocytosis: From Fundamental Science to Clinical Research - Lin, Lirong; Tian, En; Ren, Jiangwen; Wu, Zhifeng; Deng, Junhui; Yang, Jurong (Frontiers in Pharmacology, 2022)
Podocytes form a key component of the glomerular filtration barrier. Damage to podocytes is referred to as “podocyte disease.” There are many causes of podocyte injury, including primary injury, secondary injury, and gene mutations. Primary podocytosis mostly manifests as nephrotic syndrome. At present, first-line treatment is based on glucocorticoid administration combined with immunosuppressive therapy, but some patients still progress to end-stage renal disease. In Asia, especially in China, traditional Chinese medicine (TCM) still plays an important role in the treatment of kidney diseases. This study summarizes the potential mechanism of TCM and its active components in protecting podocytes, such as repairing podocyte injury, inhibiting podocyte proliferation, reducing podocyte apoptosis and excretion, maintaining podocyte skeleton structure, and upregulating podocyte-related protein expression. At the same time, the clinical efficacy of TCM in the treatment of primary podocytosis (including idiopathic membranous nephropathy, minimal change disease, and focal segmental glomerulosclerosis) is summarized to support the development of new treatment strategies for primary podocytosis.